Eco-economic Characteristic of the Arctic Regions of Russian Far East and Possible Trends of Their Change - G. Stepanko, Nataliia; G. Tkachenko, Grigoriy (International Journal of Psychosocial Rehabilitation, 2020)
The Arctic territories are drawing increasing attention from the world community. Their uniqueness and identity, rich and diverse natural resource potential, great prospects for reclamation and development on the one hand, and harsh climate with extreme conditions, permafrost, fragile natural environment sensitive to human impact on the other hand create the problem of balancing reclamation and preservation of the features of this unique ecosystem. The prospects of these territories depend on the choice of the most reasonable, economically and environmentally sound development blueprint. The existing ecological and economic situation in these territories needs to be studied to determine possible changes in the relations of production and nature, which is the purpose of this study. The methods of comparative statistical, historical, and cartographic analysis describe the studied regions, the dynamics of environmental management, and the environmental situation as a result of reclamation in the context of ulus and districts. The need and priority of activities divided by types of structural directions of environmental management are also determined.